Global Imbalances : Origins and Prospects - Servén, Luis; Nguyen, Ha (Published by Oxford University Press on behalf of the World Bank, 2015)
This paper surveys the academic and policy debate on the origins of global imbalances, their prospects after the global crisis, and their policy implications. A conventional view of global imbalances considers them to primarily result from macroeconomic policies and cyclical forces that cause demand for goods to outstrip supply in the United States and other rich countries and that have the opposite effect in major emerging markets. An alternative view holds that global imbalances are the result of structural distortions and slow-changing factors that primarily affect assets markets. This paper reviews the analytical underpinnings of these two perspectives and the empirical evidence of their respective merits. The paper then assesses the outlook for global imbalances after the crisis, particularly in terms of policy action to reduce their magnitude. Policy intervention is warranted to the extent that the imbalances are driven by welfare-reducing distortions, but in this case, the primary target of policy intervention should be the distortions rather than the imbalances. Finally, the paper examines various forms of international spillovers that may call for multilateral action to limit global imbalances.